Turn-up Plasty for Salvage of Transtibial Amputations: An Illustrated Description of the Surgical Technique. Issue 4 (October 2015) - Polfer, Elizabeth M.; Potter, Benjamin K.
Abstract : Case: We present the operative technique for turn-up plasty with a transtibial amputation in three patients with combat-related open tibial fractures who ultimately required amputation. Unaugmented amputation would have resulted in residual limbs of 7 cm; however, with use of the turn-up plasty technique, resultant limbs averaged 14 cm. All three patients achieved union at the osteosynthesis site and regular ambulation with a below-the-knee prosthesis. Conclusion: Transtibial turn-up plasty for length and level salvage is a sound option to provide robust, sensate soft-tissue coverage with additional osseous length when limb salvage fails and primary amputation would result in either an extremely short transtibial amputation or a more proximal level amputation.